The effect of service quality and customer satisfaction on the flip app customer loyalty in Indonesia - Sukandar, Galang Pramudika; Febrianta, Mochamad Yudha (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The increase in digital banking transactions in Indonesia has spawned various innovations in the field of financial technology, one of which is the digital payment application Flip.id. Despite offering free bank transfer services, Flip.id faces challenges in maintaining customer loyalty due to the large number of negative reviews. Relevant to the increasingly fierce competition with similar applications, Flip.id needs to differentiate itself by focusing on service quality and customer satisfaction. This study aims to analyze the extent to which service quality and customer satisfaction affect Flip.id user loyalty. This research uses a quantitative approach with a causal-comparative design. The research population is all Flip.id users in Indonesia, totaling 12,000,000 people. A sample of 400 respondents was selected by simple randomization. Data analysis was carried out using multiple linear regression with the help of SPSS version 26 software, as well as descriptive analysis to provide an overview of the data. The results showed that both service quality and customer satisfaction partially and simultaneously had a significant effect on Flip.id customer loyalty. The combined contribution of the two variables to customer loyalty reached 69.9%. This finding indicates that improving service quality and customer satisfaction is an effective strategy to increase Flip.id user loyalty. Thus, companies need to focus on efforts to improve service quality and ensure customer satisfaction to maintain market share and face increasingly fierce competition in the fintech industry.